Nano-hydroxyapatite as a delivery system for promoting bone regeneration in vivo: a systematic review - Mohd Zaffarin, Anis Syauqina; Shiow, Fern Ng; Min, Hwei Ng; Hassan, Haniza; Alias, Ekram (MDPI, 2021)
Nano-hydroxyapatite (nHA) has been widely used as an orthopedic biomaterial and vehicle for drug delivery owing to its chemical and structural similarity to bone minerals. Several studies have demonstrated that nHA based biomaterials have a potential effect for bone regeneration with very minimal to no toxicity or inflammatory response. This systematic review aims to provide an appraisal of the effectiveness of nHA as a delivery system for bone regeneration and whether the conjugation of proteins, antibiotics, or other bioactive molecules to the nHA further enhances osteogenesis in vivo. Out of 282 articles obtained from the literature search, only 14 articles met the inclusion criteria for this review. These studies showed that nHA was able to induce bone regeneration in various animal models with large or critical-sized bone defects, open fracture, or methicillin-resistant Staphylococcus aureus (MRSA)-induced osteomyelitis. The conjugations of drugs or bioactive molecules such as bone-morphogenetic protein-2 (BMP-2), vancomycin, calcitriol, dexamethasone, and cisplatin were able to enhance the osteogenic property of nHA. Thus, nHA is a promising delivery system for a variety of compounds in promoting bone regeneration in vivo.